2020
DOI: 10.1111/adb.12872
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid amide hydrolase is lower in young cannabis users

Abstract: We have recently shown that levels of fatty acid amide hydrolase (FAAH), the enzyme that metabolizes the endocannabinoid anandamide, are lower in the brains of adult cannabis users (CUs) (34 ± 11 years of age), tested during early abstinence. Here, we examine replication of the lower FAAH levels in a separate, younger cohort (23 ± 5 years of age). Eighteen healthy volunteers (HVs) and fourteen CUs underwent a positron emission tomography scan using the FAAH radioligand [ 11 C]CURB. Regional [ 11 C]CURB binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 47 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…No biological mechanism for these associations has been identified. Prior reports showing significantly lower brain FAAH in cannabis use disorders (24,25) position FAAH as a potential molecular link between cannabis use and psychosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…No biological mechanism for these associations has been identified. Prior reports showing significantly lower brain FAAH in cannabis use disorders (24,25) position FAAH as a potential molecular link between cannabis use and psychosis.…”
Section: Discussionmentioning
confidence: 93%
“…Duration of untreated psychosis was calculated per participants' own recollection and clinical notes when available of commencement of symptoms until first antipsychotic exposure. The present analysis includes twenty-seven healthy control participants that have been reported in prior publications (22)(23)(24)(25).…”
Section: Participantsmentioning
confidence: 99%
“…The FAAH rs2295633 polymorphism also has been associated with posttraumatic stress disorder [ 57 ]. Other FAAH variants were genetically linked with addiction, anxiety, eating disorders, depression, and obesity [ 58 , 59 , 60 , 61 , 62 , 63 ], emphasizing the endocannabinoid system’s importance for mental health but not specifically for ADHD. Presently, it is not known whether the ADHD-associated FAAH variant reduces or increases reuptake or degradation of AEA.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected from NCU and CU prior to the injection of PET radiotracers scan for previous studies reported elsewhere (Da Silva et al, 2019; Hafizi et al, 2017; Jacobson et al, 2021; Watts et al, 2020). Whole‐blood samples were centrifuged at 3000× g for 5 min at 4°C to isolate serum.…”
Section: Methodsmentioning
confidence: 99%
“…With its legalization in several countries, including Canada, stigmatization of cannabis use has steadily decreased (Budney et al, 2007; CRIME, 2011; Jacobson et al, 2021). Cannabis is a plant of the Cannabaceae family and contains several active phytocannabinoids, among which delta9‐tetrahydrocannabinol (D 9 ‐THC) and cannabidiol (CBD) are the most studied.…”
Section: Introductionmentioning
confidence: 99%